NOTE ON THE PREDATION ON PEARL OYSTER PINCTADA FUCATA (GOULD) BY SOME GASTROPODS - Chellam, A; Velayudhan, T S; Dharmaraj, S; Victor, A C C; Gandhi, A D (Indian Journal of Fisheries, 2011)
Considerable mortality of young pearl oyster, Pinctada fucata, was noticed on the oyster beds in Gulf of Mannar due to predation by gastropods, Cymatium cingulatum and Murex virgineus. Pearl oysters reared in the farm also suffered mortality, due to accidental transplantation of C. cingulatum while stocking